(untitled) (Global Conference on Medical and Health Sciences, 2026)
Robotic-assisted neurosurgery has emerged as a transformative advancement in modern surgical practice, offering enhanced precision, stability, and reproducibility in complex brain procedures. By integrating robotic systems with advanced imaging and navigation technologies, neurosurgeons can achieve greater accuracy in tumor resection, stereotactic interventions, and minimally invasive procedures.